Research Verification of Single‐ and Multiple‐Batch Production Practices at Two Channel Catfish Farms in Western Alabama. (24th July 2020) - Hanson, Terrill R.; Bott, Lisa B.; Chappell, Jesse A.; Whitis, Gregory N.; Kelly, Anita M.; Roy, Luke A.
Abstract: Aquaculture verification programs are designed to demonstrate and test research‐based recommendations on commercial‐scale operations. From 2010 to 2013, three management protocols were followed on two Channel Catfish Ictalurus punctatus farms in western Alabama. They were an owner‐defined multiple‐batch (MB) system, an Alabama Cooperative Extension System (hereafter, "Extension")‐defined single‐batch (SB) system, and an Extension‐defined MB system. Three ponds on each farm accommodated the three treatment systems. Data were collected for two completed SB cycles per farm and the two continuous MB systems over the 37‐month period on each farm. The data were combined from the two farms by management system, and averages were calculated for the following production parameters: production period, stocking, water quality, harvest, size distribution, survival, and feed conversion ratio (FCR). Enterprise budgets were developed for each management approach and compared. The feed conversion ratio was found to be the most efficient for the Extension‐defined SB (1.91), followed by the Extension‐defined MB system (2.46) and the owner‐defined MB system (2.63). While the owner‐defined MB system had the greater harvest weight, it also had the longest production period, greatest weigh‐back pounds, and least efficient FCR, resulting in a net return above all costs ($334/acre yearly) below that of the Extension‐defined SB ($553/acre yearly) and MB ($393/acre yearly) systems. This converse finding is due to the owner‐defined MB having higher costs for feed, harvest and transport, diesel, and interest on operating costs. The Extension‐defined SB and MB systems recommended feeding 90% of a weekly determined satiation‐feeding amount, resulting in reduced overall feeding, without diminishing fish growth, and a more efficient FCR. The results from this study showed that all three systems were profitable, with the net return from the Extension‐defined SB system being higher than that from the Extension‐ and owner‐defined MB systems ($160 and $219/acre yearly, respectively). Yield verification programs provide detailed production and economic knowledge of farm management system effects.